(untitled) (Current Horticulture, 2024)
The experiment was conducted at Instructional Research Farm, School of Agricultural Sciences and Rural Development, Nagaland University, Nagaland during November 2017-August 2018 in a randomized block design with three replications and seven treatments of different boron sources, viz., Agricol 5 g, Agricol 10 g, Chemibor P 5 g, Chemibor-P 10 g, Disodium Octaborate Tetrahydrate 5 g, Disodium Octaborate Tetrahydrate 10 g and the control (distilled water). The aqueous solution of boron was applied on the soil at two stages, i.e. before flowering and at pea-sized stage. Data were collected from N-E and S-W aspects of the tree canopy. The earliest panicle emergence, minimum number of days for 50% flowering (22.51 and 22.07), days to fruit set time (57.27 and 56.82) and days to harvesting from panicle initiation (168.26 and 168.00) were obtained with Agricol (5 g) on N-E and S W aspects of the canopy respectively. Maximum fruit yield (46.2 and 45.92 kg/tree) significantly increased with Agricol (5 g) application. The number of hermaphrodite flower/panicle (208.55 and 207.71), sex ratio/panicle (0.66 and 0.61) and least fruit drop (51.23 and 50.50) were found maximum with application of DOT (5g). The pulp weight (153.23 and 152.04) and fruit quality parameters significantly increased with Agricol (5 g) application. The maximum fruit length (9.38 and 9.17 cm) and width were recorded with application of Chemibor-P and fruit bioactive compounds like vitamin C (65.31 mg/100g pulp and 65.64 mg/100g pulp) and beta-carotene (3330.55 µg/100g and 3315.18 µg/100g) were recorded maximum with application of DOT (10g) on north-east and south west canopy of the plant. The lower concentrations of boron from various sources performed better in the present study.